2016
DOI: 10.1002/2016wr019400
|View full text |Cite
|
Sign up to set email alerts
|

Plausibility of freshwater lenses adjacent to gaining rivers: Validation by laboratory experimentation

Abstract: The occurrence of freshwater lenses in saline aquifers adjoining gaining rivers has recently been demonstrated as being theoretically possible by way of analytical solution. However, physical evidence for freshwater lenses near gaining rivers is limited largely to airborne geophysical surveys. This paper presents the first direct observations of freshwater lenses adjacent to gaining rivers, albeit at the laboratory‐scale, as validation of their plausibility. The experimental conditions are consistent with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 37 publications
(68 reference statements)
6
40
0
Order By: Relevance
“…Werner and Laattoe (2016) showed that gaining‐river riparian lenses are caused by buoyancy effects. They derived an analytical solution for the shape of these types of lenses (and for the corresponding saltwater discharge rates) that was verified by Werner et al (2016) through laboratory experimentation. Werner (2017) subsequently added a correction term to the analytical solution of Werner and Laattoe (2016) to correct for the dispersive mixing that was neglected in assuming of freshwater‐saltwater immiscibility.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Werner and Laattoe (2016) showed that gaining‐river riparian lenses are caused by buoyancy effects. They derived an analytical solution for the shape of these types of lenses (and for the corresponding saltwater discharge rates) that was verified by Werner et al (2016) through laboratory experimentation. Werner (2017) subsequently added a correction term to the analytical solution of Werner and Laattoe (2016) to correct for the dispersive mixing that was neglected in assuming of freshwater‐saltwater immiscibility.…”
Section: Introductionmentioning
confidence: 81%
“…Previous studies of Werner and Laattoe (2016), Werner et al (2016), and Werner (2017) presumed that the gaining freshwater river penetrates the entire depth of the aquifer. However, it is clear in geological and geophysical survey cross sections that the floodplains where riparian lenses were first encountered contain rivers that are incised only partly through the host aquifer (e.g., Munday et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…The current research aims to explore the degree to which evaporation and its modification by salt efflorescence alter previous conceptual models of riparian freshwater lenses (e.g., Laattoe et al, 2017; Werner, 2017; Werner et al, 2016; Werner & Laattoe, 2016). These studies were inspired by the occurrence of freshwater lenses within the floodplains of the MDB.…”
Section: Introductionmentioning
confidence: 99%
“…Second, salt accumulation at the soil surface by evaporation may cause density‐driven transport of high‐salinity groundwater into the aquifer and possibly reduce the lateral extent of the lens. The complex effects of vegetation, including characterization of vegetation assemblages and root growth (Slavich, 1997), and interrelationships between root water uptake and soil and aquifer salinity levels (Cramer et al, 1999; Thorburn et al, 1995), were neglected in the current analysis, which aims to provide stepwise improvement to previous research (e.g., Werner et al, 2016; Werner & Laattoe, 2016) by adding a relatively simple representation of evaporation. It should also be noted that significant regions of bare soil occur within floodplains such as those of the MDB (e.g., Holland et al, 2013), and therefore, the lack of vegetation in the conceptual models of this study is consistent with at least some parts of real‐world settings, albeit most near‐river riparian zones are more likely vegetated.…”
Section: Introductionmentioning
confidence: 99%
“…Their solution drew on a theory used in studying the extent of seawater in coastal aquifers. Laboratory experimentation by Werner et al () verified the applicability of the Werner and Laattoe () analytical solution, at least under controlled sand tank conditions.…”
Section: Introductionmentioning
confidence: 88%